CPEB2 Is Necessary for Proper Porcine Meiotic Maturation and Embryonic Development - Prochazkova, Barbora; Komrskova, Pavla; Kubelka, Michal (International journal of molecular sciences, 2018)
Oocyte meiotic maturation and embryogenesis are some of the most important physiological processes that occur in organisms, playing crucial roles in the preservation of life in all species. The post-transcriptional regulation of maternal messenger ribonucleic acids (mRNAs) and the post-translational regulation of proteins are critical in the control of oocyte maturation and early embryogenesis. Translational control affects the basic mechanism of protein synthesis, thus, knowledge of the key components included in this machinery is required in order to understand its regulation. Cytoplasmic polyadenylation element binding proteins (CPEBs) bind to the 3'-end of mRNAs to regulate their localization and translation and are necessary for proper development. In this study we examined the expression pattern of cytoplasmic polyadenylation element binding protein 2 (CPEB2) both on the mRNA (by real-time quantitative reverse transcription polymerase chain reaction, qRT-PCR) and protein (by Western blotting, WB) level, as well as its localization during the meiotic maturation of porcine oocytes and early embryonic development by immunocytochemistry (ICC). For the elucidation of its functions, CPEB2 knockdown by double-strand RNA (dsRNA) was used. We discovered that CPEB2 is expressed during all stages of porcine meiotic maturation and embryonic development. Moreover, we found that it is necessary to enable a high percentage of oocytes to reach the metaphase II (MII) stage, as well as for the production of good-quality parthenogenetic blastocysts.
Keywords: Female; Gene Knockdown Techniques; prasata; Animals; CPEBs; 3' Untranslated Regions; Oocytes; translational control; oocyte maturation; RNA-Binding Proteins; meióza; Meiosis; Parthenogenesis; Embryonic Development; proteiny vázající RNA; těhotenství; embryonic development; vývojová regulace genové exprese; partenogeneze; zvířata; RNA, Messenger; genový knockdown; messenger RNA; embryonální vývoj; ženské pohlaví; 3' nepřekládaná oblast; Swine; Pregnancy; oocyty; CPEB2; Gene Expression Regulation, Developmental